2020
DOI: 10.3892/ijmm.2020.4515
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill exercise promotes neurogenesis and myelin repair via upregulating Wnt/β‑catenin signaling pathways in the juvenile brain following focal cerebral ischemia/reperfusion

Abstract: Physical exercise has a neuroprotective effect and is an important treatment after ischemic stroke. Promoting neurogenesis and myelin repair in the penumbra is an important method for the treatment of ischemic stroke. However, the role and potential mechanism of exercise in neurogenesis and myelin repair still needs to be clarified. The goal of the present study was to ascertain the possible effect of treadmill training on the neuroprotective signaling pathway in juvenile rats after ischemic stroke. The model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 73 publications
1
32
0
Order By: Relevance
“…A recent study reported that motor exercise stimulated the canonical Wnt/β-catenin pathway for recovering from focal cerebral ischemic reperfusion injury in juvenile rats. Motor activity regulated canonical Wnt/β-catenin pathway and promoted neurogenesis and myelin repair [ 19 ]. Another study reported that electroacupuncture in multiple acupoints of a paralyzed limb stimulated the proliferation of neural progenitor cells through the activation of the Wnt/β-catenin signaling pathway and suppression of GSK-3β [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported that motor exercise stimulated the canonical Wnt/β-catenin pathway for recovering from focal cerebral ischemic reperfusion injury in juvenile rats. Motor activity regulated canonical Wnt/β-catenin pathway and promoted neurogenesis and myelin repair [ 19 ]. Another study reported that electroacupuncture in multiple acupoints of a paralyzed limb stimulated the proliferation of neural progenitor cells through the activation of the Wnt/β-catenin signaling pathway and suppression of GSK-3β [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The BDNF gene has a rather complex structure and can express different mRNA isoforms through alternative splicing, producing 28-to 37-kDa precursors. The mature form is expected to be approximately 14 kDa (monomer) and the dimer is approximately 28 kDa [39][40][41][42] . Therefore, the 28-kDa protein in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of Wnt signaling were also observed in the cells of oligodendroglial lineage. Myelin repair in the ischemic penumbra was increased after treadmill exercise, and this effect was abolished after the treatment with Wnt signaling inhibitor XAV939, suggesting a possible role of active Wnt signaling in NG2 glia-cells known for their role in remyelination [173]. The differentiation of these cells to myelinating mature oligodendrocytes was also enhanced by the trophic factor tissue inhibitor of metalloproteinases 1 (TIMP1).…”
Section: The Impact Of Wnt Signaling On Different Cell Types During Imentioning
confidence: 99%